Enhancing Police Efficiency in Detecting Crime in Hong Kong. - Wong, Gabriel T. W.; Manning, Matthew (Crime, Law & Social Change, 2022)
In this study we examine how the process of crime detection by frontline and investigative police can be modified so that the same level of policing inputs (i.e. police strength) can produce more outcomes (i.e. crime detection rate). A pooled frontier analysis method is used to measure the relative efficiency of 18 police districts in Hong Kong from 2007 to 2015 (n = 18 districts × 9 years = 162 decision making units (DMUs)), demonstrating variable returns-to-scale. Findings reveal that 95 of the 162 DMUs were found to be inefficient compared to the benchmark DMUs (those police districts identified by the Free Disposable Hull (FDH) approach as efficient) with an average FDH efficiency score of 95.37 out of a possible score of 100. Efficient districts provide an exemplar on how an inefficient district could achieve an optimal input–output translation for the detection of crime. This evidence can be used to shape police policy at the district level. This study represents the first frontier analysis of police efficiency in the detection of crime in Hong Kong using the most recent efficiency technique. We produce evidence that can inform police policy regarding the deployment of finite resources that improve the efficiency of detection without compromising other institutional targets.